Cannabis related side effects in otolaryngology: a scoping review - Jobanjit S. Phulka; Joel W. Howlett; Amanda Hu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Cannabis has been rapidly legalized in North America; however, limited evidence exists around its side effects. Health Canada defines side effect as a harmful and unintended response to a health product. Given drug safety concerns, this study’s purpose was to review the unintended side effects of cannabis in otolaryngology. Methods The Preferred Reporting Items For Systematic Reviews and Meta-analysis extension for Scoping Reviews (PRISMA-ScR) protocol was used to conduct a scoping review of the MEDLINE, EMBASE, CINAHL, and CENTRAL databases. (PROSPERO: CRD42020153022). English studies in adults were included from inception to the end of 2019. In-vitro, animal, and studies with n < 5 were excluded. Primary outcome was defined as unintended side effects (defined as any Otolaryngology symptom or diagnosis) following cannabis use. Oxford Centre for Evidence-Based Medicine: Levels of Evidence and risk of bias using the Risk of Bias in randomized trials (RoB 2) and Risk of Bias in Non-Randomized Studies of Interventions (ROBINS-I) tools were assessed.. Two authors independently reviewed all studies; the senior author settled any discrepancies. Results Five hundred and twenty-one studies were screened; 48 studies were analysed. Subspecialties comprised: Head and Neck (32), Otology (8), Rhinology (5), Airway (5), Laryngology (1). Cannabis use was associated with unintended tinnitus, vertigo, hearing loss, infection, malignancy, sinusitis, allergic rhinitis, thyroid dysfunction, and dyspnea. About half (54.1%) of studies showed increased side effects, or no change in symptoms following cannabis use. Oxford Levels of Evidence was 2–4 with substantial heterogeneity. Risk of bias assessment with RoB2 was low to high and ROBINS-1 was moderate to critical. Conclusion This was the first comprehensive scoping review of unintended side effects of cannabis in Otolaryngology. The current literature is limited and lacks high-quality research Future randomized studies are needed to focus on therapeutic effects of cannabis in otolaryngology. Substantial work remains to guide clinicians to suggest safe, evidence-based choices for cannabis use. Graphic abstract